(untitled) (Neo Science Peer Reviewed Journal, 2023)
The processes taking place in the modern biosphere affect the human body, for example, the imbalance, deficiency and excess of micronutrients cause pathological changes, and among them there are synergistic and antagonistic conditions. Our food additive made from cabbage leaves is the main source of macro and micronutrients.